The Roles of Maternal Depression, Serotonin Reuptake Inhibitor Treatment, and Concomitant Benzodiazepine Use on Infant Neurobehavioral Functioning Over the First Postnatal Month - Salisbury, Amy L. (Am J Psychiatry, 2015)
OBJECTIVE: The purpose of this article was to systematically compare the developmental trajectory of neurobehavior over the first postnatal month for infants with prenatal exposure to pharmacologically untreated maternal depression, selective serotonin reuptake inhibitors or serotonin and norepinephrine reuptake inhibitors (collectively: SSRIs), SSRIs with concomitant benzodiazepines (SSRI plus benzodiazepine), and no maternal depression or drug treatment (no exposure). METHOD: Women (N=184) were assessed at two prenatal time points to determine psychiatric diagnoses, symptom severity, and prenatal medication usage. Infants were examined with a structured neurobehavioral assessment (Neonatal Intensive Care Unit Network Neurobehavioral Scale) at multiple time points across the first postnatal month. SSRI exposure was confirmed in a subset of participants with plasma SSRI levels. General linear-mixed models were used to examine group differences in neurobehavioral scores over time with adjustment for demographic variables and depression severity. RESULTS: Infants in the SSRI and SSRI plus benzodiazepine groups had lower motor scores and more CNS stress signs across the first postnatal month, as well as lower self-regulation and higher arousal at day 14. Infants in the depression group had low arousal throughout the newborn period. Infants in all three clinical groups had a widening gap in scores from the no-exposure group at day 30 in their response to visual and auditory stimuli while asleep and awake. Infants in the SSRI plus benzodiazepine group had the least favorable scores on the Neonatal Intensive Care Unit Network Neurobehavioral Scale. CONCLUSIONS: Neonatal adaptation syndrome was not limited to the first 2 weeks postbirth. The profile of neurobehavioral development was different for SSRI exposure than depression alone. Concomitant benzodiazepine use may exacerbate adverse behavioral effects.